Ein quantitatives Szenario des Übergangs vom bestehenden System der Alterssicherung auf ein System der Grundsicherung für alle - Derik Burgert; Hugo Dicke; Hans H. Glismann; Ernst-Jürgen Horn (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
This paper is concerned with establishing the data base that is necessary to analyse the double bürden argument which has been used to reject a sweeping reform of the German old-age pension System. We show that this argument does not hold if the existing pay-as-you-go system were to be replaced with a System of tax-funded flat-rate payments for the old. We provide some 80 tables containing estimates of Claims on the public-pension System in the year 2000 (the postulated year of transition) and projections of Claims on a future system of flat-rate old-age payments.
Keywords: H55; 330; Gesetzliche Krankenversicherung; Rentenreform; Mindestrente; Wirkungsanalyse; Rentenfinanzierung; Deutschland